The pastoral farming system: Balancing between tradition and transition - Leeuw, Jan de; Osano, Philip M.; Said, Mohammed; Ayantunde, Augustine A.; Dube, Sikhalazo; Neely, Constance; Vrieling, Anton; Thornton, Philip K.; Ericksen, Polly J. (Routledge, 2019)
Key messages